An all-inorganic CsPbI2Br perovskite solar cell based on inorganic ammonium salt vapor-phase assisted crystallization passivation, its fabrication method and application
Patent Information
- Application Number
- CN202610977240.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-10-16
AI Technical Summary
本发明提供了高效全无机CsPbI2Br钙钛矿太阳能电池能够解决现有CsPbI2Br钙钛矿薄膜结晶过程难以调控、表面和晶界缺陷较多、溶液后处理易造成表面损伤和钝化不均的问题,具有应用价值
[0033] 1. A further innovation of this invention lies in the fact that NH3 and HCl perform different but complementary functions in the same gas-phase treatment process: NH3 mainly plays a "dynamic coordination regulation" role, used to delay crystallization, promote crystal rearrangement, and passivate uncoordinated Pb²⁺; HCl mainly plays a "surface chemical fixation" role, used to construct Cl-related passivation layers, compensate for halogen vacancies, and inhibit ion migration. When the two work synergistically, they can simultaneously improve the bulk crystal quality, surface defect state, and grain boundary stability of the CsPbI₂Br thin film, resulting in perovskite thin films with lower defect density, fewer non-radiative recombination centers, and stronger resistance to thermo-photoaging.
Smart Images

Figure CN122934951A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new materials and new energy photovoltaic devices, specifically relating to an all-inorganic CsPbI2Br perovskite solar cell based on inorganic ammonium salt vapor-phase assisted crystallization passivation, its preparation method and application. Background Technology
[0002] Solar cells are one of the most important technologies for directly utilizing solar energy. Perovskite solar cells have attracted widespread attention in recent years due to their advantages such as high absorption coefficient, long carrier diffusion length, high defect tolerance, solution-processability, and low fabrication cost. Compared with organic-inorganic hybrid perovskites, all-inorganic cesium lead halide perovskites do not contain easily volatile or decomposed organic A-site cations, and generally exhibit better thermal and compositional stability. Among them, CsPbI₂Br combines a suitable band gap, high thermal stability, and good phase stability, making it one of the important light-absorbing materials for all-inorganic perovskite solar cells.
[0003] However, the crystallization process of CsPbI2Br films is relatively rapid, and during the wet film, mesophase, and final perovskite phase transformation, grain size inhomogeneity, porosity, surface roughness, grain boundary defects, halogen vacancies, and uncoordinated Pb are prone to occur. 2+ These defects can induce nonradiative recombination, reducing open-circuit voltage, short-circuit current, and fill factor, and accelerating ion migration and device degradation under environmental stresses such as humidity, heat, and light. Especially in the one-step preparation of CsPbI₂Br films, the precursor solvent evaporation and crystal nucleation growth processes occur simultaneously, making precise control of film crystallization kinetics difficult.
[0004] Currently, commonly used perovskite defect passivation methods mainly include precursor additive engineering, interface modification, and solution post-treatment. While these methods can improve film quality, solution post-treatment is often affected by solvent evaporation, solution concentration fluctuations, and uneven local wetting, which can easily lead to uneven distribution of the passivating agent and may cause secondary dissolution or damage to the soft perovskite surface. Furthermore, traditional post-treatment often occurs after the perovskite film has fully crystallized, making it difficult to simultaneously control the crystallization and defect passivation processes.
[0005] Gas-phase processing offers advantages such as uniform molecular diffusion, absence of liquid solvent residue, mild contact methods, and ease of scale-up, and is gradually becoming an important direction for the control of perovskite film crystallization and surface passivation. Previous studies have shown that small molecule gases such as NH3 can participate in the perovskite crystallization process and interact with uncoordinated Pb. 2+Through interaction, halogen-related gases can participate in halogen vacancy repair and grain boundary defect passivation. Therefore, if a gaseous environment released by inorganic ammonium salts can be constructed at the critical stage of the transformation from the CsPbI2Br mesophase to the final perovskite phase, allowing crystallization regulation and defect passivation to occur simultaneously, it is expected to form high-quality all-inorganic perovskite thin films and improve battery performance and stability. Summary of the Invention
[0006] Based on the above-mentioned technological needs, the purpose of this invention is to provide an all-inorganic CsPbI₂Br perovskite solar cell based on inorganic ammonium salt vapor-phase assisted crystallization passivation, its preparation method, and its application. This invention proposes an inorganic ammonium salt vapor-phase assisted crystallization passivation strategy: after the formation of the CsPbI₂Br mesophase film but before complete high-temperature crystallization, a vapor-phase treatment environment is generated by preheating the inorganic ammonium salt, briefly exposing the perovskite mesophase film to an atmosphere containing NH₃ and hydrogen halides. This simultaneously achieves crystallization kinetic control, halogen vacancy repair, and passivation of uncoordinated lead defects. This method does not require the direct introduction of a large amount of passivating agent into the perovskite precursor, nor does it require additional solution post-treatment. The process is simple and suitable for integration with the all-inorganic CsPbI₂Br solar cell preparation process. This invention provides a high-efficiency all-inorganic CsPbI₂Br perovskite solar cell that solves the problems of difficult-to-control crystallization process, numerous surface and grain boundary defects, and surface damage and uneven passivation caused by solution post-treatment in existing CsPbI₂Br perovskite films, and has application value.
[0007] To achieve the above-mentioned objectives, the present invention employs the following technical solution:
[0008] This invention provides a method for fabricating an all-inorganic CsPbI2Br perovskite solar cell based on inorganic ammonium salt vapor-phase assisted crystallization passivation. The fabrication method specifically includes the following steps:
[0009] (1) Preparation of SnO2 quantum dot solution: SnCl2 and thiourea were dissolved in deionized water and stirred, centrifuged, precipitate removed, and filtered to obtain SnO2 quantum dot solution;
[0010] (2) Preparation of SnO2 electron transport layer: The SnO2 quantum dot solution and FTO conductive glass are preheated respectively. After preheating, the SnO2 quantum dot solution is spin-coated onto the FTO conductive glass to obtain FTO / SnO2 substrate;
[0011] (3) TiCl4 modification treatment: The FTO / SnO2 substrate was placed in a TiCl4 aqueous solution for water bath treatment, followed by rinsing and annealing to obtain FTO / SnO2-TiO2. x Cl 4-2x A basis, where x ≤ 2;
[0012] (4) Preparation of CsPbI2Br precursor solution: CsI, PbI2 and PbBr2 are dissolved in a polar organic solvent to obtain CsPbI2Br precursor solution;
[0013] (5) Preparation of CsPbI2Br mesophase thin film: The CsPbI2Br precursor solution was spin-coated onto the FTO / SnO2-TiO2 film. x Cl 4-2x On the substrate, hot air assisted film formation was performed during spin coating to obtain a CsPbI2Br mesophase film;
[0014] (6) Preparation of CsPbI2Br perovskite film: Inorganic ammonium salt is placed in a closed chamber for preheating treatment to release gas and form a gas phase treatment environment; the CsPbI2Br mesophase film is placed in the gas phase treatment environment for gas phase assisted crystallization passivation treatment, and the passivation treatment is heated and annealed to obtain CsPbI2Br perovskite film.
[0015] (7) Carbon electrode preparation: Carbon paste is coated on the CsPbI2Br perovskite film and heated for annealing to obtain an all-inorganic CsPbI2Br perovskite solar cell.
[0016] Furthermore, in step (1), the molar ratio of SnCl2 to thiourea is 0.8~1.2:1, and the molar concentration of SnCl2 is 0.1 mol / L~0.5 mol / L.
[0017] Furthermore, the preheating temperature of the SnO2 quantum dot solution in step (2) is 70°C. o C~90 o C, the preheating time is 3 min to 9 min; the preheating time of the FTO conductive glass is 1 min to 5 min; the spin coating speed is 1000 to 2000 rpm, and the spin coating acceleration is 500 to 1200 rpm / s.
[0018] Furthermore, in step (3), the volume concentration of the TiCl4 aqueous solution is 400 μL / mL to 600 μL / mL, and the temperature of the water bath treatment is 60°C. o C~100 o C, the water bath treatment time is 20 min to 50 min.
[0019] Furthermore, in step (3), the annealing process involves rinsing the water-bath treated FTO / SnO2 substrate with ethanol, then annealing it on a heating platform at a temperature of 180°C. o C~220 o C, annealing time is 25~40 min.
[0020] Furthermore, in step (4), the molar ratio of CsI, PbI2 and PbBr2 is (1.8~2.2):(0.8~1.2):(0.8~1.2).
[0021] Furthermore, the molar ratio of CsI, PbI2 and PbBr2 is preferably 2:1:1.
[0022] Furthermore, in step (4), the polar organic solvent is a methyl ammonium chloride solution, and the solvent of the methyl ammonium chloride solution is dimethyl sulfoxide.
[0023] Furthermore, the spin coating in step (5) adopts a two-step spin coating process, specifically including: the first step spin coating: the rotation speed is 500 rpm~2000 rpm, and the time is 5 s~20 s; the second step spin coating: the rotation speed is 2500 rpm~5000 rpm, and the time is 20 s~60 s.
[0024] Furthermore, the specific operation of hot air assisted film formation in step (5) includes: 3 s to 8 s after the spin coating begins, placing a hot air source with a temperature of 80 ℃ to 130 ℃ at a distance of 3 cm to 8 cm above the film surface and blowing until the film changes from a wet film to a dark mesophase film.
[0025] Furthermore, in step (6), the inorganic ammonium salt includes NH4Cl, the temperature of the preheating treatment is 150 ℃~170 ℃, the preheating time is 3 min~8 min, and the time of the gas phase assisted crystallization passivation treatment is 40 s~100 s.
[0026] Furthermore, the amount of NH4Cl used is 0.04~0.08 mg / cm³. 3 .
[0027] Furthermore, in step (6), the heating annealing temperature is 240 ℃~290 ℃, and the time is 5 min~20 min.
[0028] Furthermore, in step (7), the carbon paste is formed into a carbon electrode by scraping, screen printing, spraying or scraper coating; the annealing temperature of the carbon electrode is 70 ℃~120 ℃, and the annealing time is 5 min~30 min.
[0029] The present invention also provides an all-inorganic CsPbI2Br perovskite solar cell prepared by the aforementioned preparation method.
[0030] This invention also provides the application of the aforementioned all-inorganic CsPbI2Br perovskite solar cell in the fabrication of solar cell modules, photovoltaic power generation devices, portable power supply devices, or power stations.
[0031] Furthermore, the open-circuit voltage of the all-inorganic CsPbI2Br perovskite solar cell is 1.15~1.33V, and the short-circuit current is 12 mA·cm⁻¹. -2 ~14.8 mA·cm -2 The fill factor is 0.70~0.82, and the photoelectric conversion efficiency is 13%~15.5%.
[0032] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:
[0033] 1. A further innovation of this invention lies in the fact that NH3 and HCl perform different but complementary functions in the same gas-phase treatment process: NH3 mainly plays a "dynamic coordination regulation" role, used to delay crystallization, promote crystal rearrangement, and passivate uncoordinated Pb²⁺; HCl mainly plays a "surface chemical fixation" role, used to construct Cl-related passivation layers, compensate for halogen vacancies, and inhibit ion migration. When the two work synergistically, they can simultaneously improve the bulk crystal quality, surface defect state, and grain boundary stability of the CsPbI₂Br thin film, resulting in perovskite thin films with lower defect density, fewer non-radiative recombination centers, and stronger resistance to thermo-photoaging.
[0034] 2. The CsPbI₂Br perovskite solar cell prepared using the inorganic ammonium salt vapor-phase assisted crystallization passivation strategy described in this invention achieves a maximum photoelectric conversion efficiency of 15.53% and an open-circuit voltage of 1.322 V. After storage at ISOS-D-2 and 85 °C for 180 days, it retains 87% of its initial efficiency, and after continuous operation under illumination for 670 h, the efficiency remains at 75.5% of its initial value. Experimental results show that this invention can not only effectively improve the photovoltaic performance of CsPbI₂Br perovskite solar cells, but also significantly enhance the thermal stability and illumination stability of the device, which has important application value for promoting the efficient and stable preparation of all-inorganic perovskite solar cells.
[0035] 3. This invention introduces inorganic ammonium salt gas-phase auxiliary treatment during the annealing and crystallization process of CsPbI2Br perovskite. Utilizing the NH3 and HCl gas-phase active components released by heated NH4Cl, the crystallization process and surface / grain boundary defect states of the CsPbI2Br film are simultaneously regulated. Unlike traditional solution post-treatment, this gas-phase treatment does not introduce additional solvents, avoiding problems such as secondary dissolution of the perovskite surface, solvent residue, and uneven distribution of passivating agent concentration. This allows the active gas components to act more uniformly on the perovskite film surface, grain boundaries, and shallow defect regions, thereby achieving synergistic crystallization regulation and defect passivation. Attached Figure Description
[0036] Figure 1The image shows the in-situ UV-vis absorption spectrum evolution of the CsPbI2Br perovskite film prepared in this invention during the annealing process, where a represents the untreated CsPbI2Br film and b represents the CsPbI2Br film treated with NH4Cl gas phase assistance.
[0037] Figure 2 The image shows the in-situ PL spectral evolution of the CsPbI2Br perovskite thin film prepared in this invention during the annealing process. In the image, a and b are the PL spectra of the untreated and NH4Cl gas-phase treated CsPbI2Br thin films at different annealing times, respectively; c and d are the in-situ two-dimensional evolution diagrams of the PL intensity of the untreated and NH4Cl gas-phase treated CsPbI2Br thin films, respectively.
[0038] Figure 3 The images show a comparison of PLQY and QFLS of the CsPbI2Br perovskite films prepared in this invention and the CsPbI2Br perovskite films after NH4Cl vapor phase treatment.
[0039] Figure 4 The XRD characterization results of the CsPbI2Br perovskite prepared in this invention and the CsPbI2Br perovskite after NH4Cl gas phase treatment are shown. In the figure, a is a comparison of the diffraction peak positions of the main crystal planes, and b is a statistical diagram of the intensity of the corresponding characteristic diffraction peaks.
[0040] Figure 5 SEM images and particle size statistics of the CsPbI2Br perovskite film prepared in this invention and the CsPbI2Br perovskite film after NH4Cl vapor phase treatment.
[0041] Figure 6 The image shows a cross-sectional SEM image of the CsPbI2Br perovskite prepared in this invention and the CsPbI2Br perovskite after NH4Cl vapor phase treatment.
[0042] Figure 7 The images show the AFM surface morphology and height profile of the CsPbI2Br perovskite prepared in this invention and the CsPbI2Br perovskite after NH4Cl vapor phase treatment. In the images, a and b are the AFM surface morphology images of the two perovskites, and c and d are the height profile images of the two perovskites along the dashed lines.
[0043] Figure 8 The image shows the AFM three-dimensional morphology and surface height distribution of the CsPbI2Br perovskite prepared in this invention and the CsPbI2Br perovskite after NH4Cl vapor phase treatment.
[0044] Figure 9The images show the TOF-SIMS depth profile of the CsPbI2Br perovskite thin film prepared in this invention, where a and b represent the PbI3 content in the CsPbI2Br thin films treated with NH4Cl liquid phase and NH4Cl gas phase, respectively. - PbBr3 - PbCl3 - and F - The signal changes with etching time. c and d are three-dimensional TOF-SIMS depth profiles of CsPbI2Br films treated with NH4Cl liquid phase and NH4Cl gas phase, respectively.
[0045] Figure 10 The images show the XPS spectra of the CsPbI2Br perovskite prepared in this invention and the CsPbI2Br perovskite after gas-phase treatment with NH4Cl, where a is the C 1s fine spectrum, b is the Cs 3d fine spectrum, c is the Pb 4f fine spectrum, d is the I 3d fine spectrum, and e is the Br 3d fine spectrum.
[0046] Figure 11 The image shows the Raman spectrum of the CsPbI2Br perovskite prepared in this invention and the CsPbI2Br perovskite after gas-phase treatment with NH4Cl.
[0047] Figure 12 The temperature-dependent conductivity test results of CsPbI2Br perovskite prepared in this invention and CsPbI2Br perovskite after gas-phase treatment with NH4Cl are shown. Among them, a and b are the linear voltammetric curves of the two at different temperatures, and c is the ion migration activation energy calculated based on the Arrhenius relation.
[0048] Figure 13 The images show the UV-vis spectra of the CsPbI2Br perovskite prepared in this invention and the CsPbI2Br perovskite after NH4Cl vapor phase treatment. In the images, a and b are the absorption evolution diagrams of both perovskite at wavelengths of 600-640 nm as a function of light irradiation, c is a photograph of the CsPbI2Br thin film after irradiation and immersion in toluene, and d is the UV-vis absorption spectrum of the toluene solution after immersion.
[0049] Figure 14 The images show the PL mapping of the untreated CsPbI2Br perovskite film and the CsPbI2Br perovskite film after NH4Cl vapor phase treatment prepared in this invention.
[0050] Figure 15 This is a schematic diagram of the test structure of the CsPbI2Br perovskite thin film prepared in this invention and its TRPL spectrum analysis. In this diagram, a is a schematic diagram of the TRPL test structure of the CsPbI2Br thin film, and b is the normalized TRPL decay curve of the CsPbI2Br thin film after untreated and NH4Cl gas phase treatment.
[0051] Figure 16 The images show the c-AFM diagrams of the CsPbI2Br perovskite prepared in this invention and the CsPbI2Br perovskite after NH4Cl vapor phase treatment, where a and b are the c-AFM surface current distribution diagrams of the two, and c and d are the current profile diagrams along the dashed lines.
[0052] Figure 17 The images show the c-AFM diagrams of the CsPbI2Br perovskite prepared in this invention and the CsPbI2Br perovskite after NH4Cl vapor phase treatment, where a and b are the three-dimensional surface current diagrams of both, and c and d are the local current distribution diagrams of both.
[0053] Figure 18 The images show the KPFM diagrams of the CsPbI2Br perovskite prepared in this invention and the CsPbI2Br perovskite after NH4Cl vapor phase treatment. In the images, a and b are the c-AFM surface potential distribution diagrams of the two perovskites, and c and d are the surface potential profile diagrams of the two perovskites along the dashed lines.
[0054] Figure 19 The images show the KPFM diagrams of the CsPbI2Br perovskite prepared in this invention and the CsPbI2Br perovskite after NH4Cl gas phase treatment, where a and b are the three-dimensional surface potential distribution diagrams of the two perovskites, and c and d are the statistical diagrams of the surface potential distribution of the two perovskites.
[0055] Figure 20 The image shows the SCLC diagram of the CsPbI₂Br perovskite prepared in this invention and the CsPbI₂Br perovskite after gas-phase treatment with NH₄Cl. In the diagram, a is the space charge confinement current curve, and b is the corresponding J... 1 / 2 -V linear fitting curve, c is the trap filling limiting voltage V TFL and the density of trapped states N t Statistical chart.
[0056] Figure 21 The image shows the UV-Vis spectra of the CsPbI2Br perovskite prepared in this invention and the CsPbI2Br perovskite after gas-phase treatment with NH4Cl, where a is the UV-Vis absorption spectrum and b is the Urbach energy obtained by fitting the absorption edge exponential tail state.
[0057] Figure 22The figures show the electrochemical performance of the CsPbI2Br perovskite prepared in this invention and the CsPbI2Br perovskite after gas-phase treatment with NH4Cl. In the figures, a is the JV curve, b and c are the forward and reverse scan JV curves and hysteresis index of the corresponding devices, d is the external quantum efficiency and integral current density curve, e is the steady-state output curve near the maximum power point, f is the Mott-Schottky curve, g is the Nyquist plot under illumination, h is the Nyquist plot under dark conditions, and i is the dark-state JV curve.
[0058] Figure 23 The image shows the stability of the CsPbI2Br perovskite prepared in this invention after gas-phase treatment with NH4Cl in an air environment. The test conditions were 25 °C and 40-50% RH.
[0059] Figure 24 The figure shows the operational stability test results of the CsPbI2Br perovskite solar cell prepared in this invention after gas-phase treatment with NH4Cl under continuous illumination. The test was conducted in accordance with the ISOS-L-1 protocol.
[0060] Figure 25 The results show the storage stability of the CsPbI2Br perovskite solar cells prepared in this invention after vapor treatment with NH4Cl at 25 °C and humidity below 5% RH. In the figures, a represents the change of normalized open-circuit voltage with storage time, b represents the change of normalized photoelectric conversion efficiency with storage time, c represents the change of normalized short-circuit current density with storage time, and d represents the change of normalized fill factor with storage time.
[0061] Figure 26 The figure shows the test results of the CsPbI2Br perovskite solar cells prepared in this invention after vapor treatment with NH4Cl. The tests were conducted at 85 °C according to the ISOS-D-2 protocol. In the figure, a represents the change of normalized open-circuit voltage with storage time, b represents the change of normalized photoelectric conversion efficiency with storage time, c represents the change of normalized short-circuit current density with storage time, and d represents the change of normalized fill factor with storage time. Detailed Implementation
[0062] The technical solution of the present invention will be further described in detail below with reference to specific embodiments.
[0063] Example 1: Preparation of an all-inorganic CsPbI2Br perovskite solar cell with NH4Cl vapor-phase assisted crystallization passivation
[0064] This embodiment provides an all-inorganic CsPbI2Br perovskite solar cell with NH4Cl vapor-phase assisted crystallization passivation. The preparation method of the all-inorganic CsPbI2Br perovskite solar cell includes the following:
[0065] 1. FTO Cleaning: Insert the FTO conductive glass into a glass cleaning rack and ultrasonically clean it for 10 minutes in a cleaning solution containing glass cleaner and deionized water, with a volume ratio of glass cleaner to deionized water of 1:50. Subsequently, ultrasonically clean it for 10 minutes each with deionized water, anhydrous ethanol, and then deionized water. Store the cleaned FTO conductive glass in anhydrous ethanol for later use.
[0066] 2. Preparation of SnO2 quantum dot solution: 0.8530 g of anhydrous SnCl2 and 0.3380 g of thiourea (CH4N2S) were dissolved in 30 mL of deionized water and stirred at room temperature to form a milky white suspension. After stirring continuously for 36 h, the system turned into a pale yellow liquid. The resulting liquid was centrifuged at 9000 rpm for 5 min to remove the precipitate, and a yellow transparent SnO2 quantum dot solution was obtained. The solution was filtered using a 0.22 μm PTFE filter for later use.
[0067] 3. Preparation of SnO2 electron transport layer: Take out the FTO conductive glass, rinse it with deionized water and anhydrous ethanol in sequence and blow it dry; place the FTO conductive glass in a plasma cleaner for 5 min; place the FTO conductive glass and SnO2 quantum dot solution on an 80 ℃ heating stage for preheating for 5 min; spin-coat 90 μL SnO2 quantum dot solution with spin-coating parameters of 2000 rpm and 30 s; anneal on a 200 ℃ heating stage for 1 h to obtain FTO / SnO2 substrate.
[0068] 4. TiCl4 Modification: 440 μL of TiCl4 was dispersed in 100 mL of deionized water to obtain a clear TiCl4 solution. The cooled FTO / SnO2 substrate was placed obliquely in the TiCl4 solution and treated in a 75 ℃ water bath for 30 min. After treatment, it was rinsed sequentially with deionized water and anhydrous ethanol, and annealed on a 200 ℃ heating stage for 30 min. After natural cooling to room temperature, FTO / SnO2-TiO2 was obtained. x Cl 4-2x A basis, where x ≤ 2.
[0069] 5. Preparation of CsPbI₂Br precursor solution: Dissolve 120 mg MACl (methylammonium chloride) in 1200 μL DMSO (dimethyl sulfoxide), and sonicate to dissolve, preparing a 100 mg / mL MACl solution. Weigh 312 mg CsI, 277 mg PbI₂, and 220 mg PbBr₂ and dissolve them in 50 μL of the above MACl solution and 950 μL DMSO, sonicate until completely dissolved, to obtain the CsPbI₂Br precursor solution.
[0070] 6. Preparation of CsPbI2Br thin films: This process consists of two steps, as detailed below:
[0071] S1: 90 μL of CsPbI2Br precursor solution was dropped onto the substrate surface for spin coating. The spin coating adopted a two-step spin coating process, specifically including: First step spin coating: the first step rotation speed was 1500 rpm, the acceleration was 1500, and the time was 10 s; the second step spin coating rotation speed was 3000 rpm, the acceleration was 3000, and the time was 30 s. After the first step spin coating ran for 5 s, hot air was used to blow away the film surface at a distance of 3 cm to 5 cm. The temperature of the hot air was 100 ℃, until the substrate turned black. The blowing time was about 10 s to 15 s, and a CsPbI2Br mesophase film was obtained.
[0072] S2: Place 1 g of NH4Cl powder in a 9 cm diameter glass petri dish and preheat it at 160 °C for 5 min to generate a gaseous environment containing NH3 and HCl in a locally enclosed environment. Quickly place the spin-coated and hot-air-assisted CsPbI2Br mesophase film into the preheated gaseous environment, maintaining the processing temperature at 160 °C for 60 s. After processing, transfer the device to a 270 °C heating stage for annealing for 10 min to form a high-quality CsPbI2Br perovskite film.
[0073] 7. Carbon electrode preparation: Carbon paste was coated onto a CsPbI2Br perovskite thin film using a blade coating method, and then annealed on a heating stage at 90 ℃ for 15 min to obtain a complete all-inorganic CsPbI2Br perovskite solar cell.
[0074] Example 2: Characterization of CsPbI2Br perovskite crystallization regulated by NH4Cl
[0075] Based on the high-quality CsPbI₂Br perovskite film prepared in Example 1, this example characterizes and measures the CsPbI₂Br perovskite film, using the CsPbI₂Br film obtained without NH₄Cl gas phase treatment as a control, to further explore its performance. The specific details are as follows:
[0076] 1. The in-situ UV-vis absorption spectra of CsPbI2Br films after annealing and after NH4Cl vapor phase treatment were measured respectively. Figure 1 As shown.
[0077] Figure 1 The dashed line indicates the time when the absorbance of the thin film begins to increase significantly, from... Figure 1 The results show that the absorbance of the untreated CsPbI₂Br film increases rapidly in the early stage of annealing, indicating that the CsPbI₂Br perovskite phase forms relatively quickly. However, the time of significant absorbance increase in the CsPbI₂Br film treated with NH₄Cl is delayed, indicating that the gas-phase treatment slows down the rapid nucleation and crystallization process of CsPbI₂Br. This phenomenon suggests that the NH₃ released by NH₄Cl upon heating can react with Pb. 2+ Transient coordination occurs, reducing Pb 2+ with I - / Br - The rapid reaction rate transforms the rapid, disordered crystallization of perovskite into a relatively slow, ordered crystal growth process, which is beneficial for crystal rearrangement, grain growth, and improved film quality.
[0078] 2. The in-situ PL spectra of CsPbI2Br films after annealing and after NH4Cl vapor phase treatment were measured respectively. Figure 2 As shown.
[0079] from Figure 2 As can be seen, the untreated CsPbI₂Br film exhibits a significant PL emission peak in the early stages of annealing, and the PL intensity rapidly increases with prolonged annealing time, indicating that the perovskite phase forms and completes the crystallization process relatively quickly. In contrast, the PL signal enhancement time of the CsPbI₂Br film treated with NH₄Cl is significantly delayed, indicating that the NH₃ / HCl gas phase component released by NH₄Cl can regulate the perovskite crystallization kinetics, suppressing instantaneous rapid nucleation and transforming the rapid crystallization process of CsPbI₂Br into a relatively slow and ordered crystal growth process. Furthermore, the final PL intensity of the CsPbI₂Br film sample treated with NH₄Cl is higher, indicating that gas phase treatment, while delaying crystallization, can also reduce defect-induced nonradiative recombination, which is beneficial for the formation of high-quality CsPbI₂Br perovskite films.
[0080] 3. The photoluminescence quantum yield (PLQY) and quasi-Fermi level splitting (QFLS) of the CsPbI2Br thin films after untreated and NH4Cl gas phase treatment were tested respectively. Figure 3 As shown.
[0081] from Figure 3The results show that the PLQY of the CsPbI₂Br film is significantly improved after NH₄Cl vapor phase treatment, indicating that the proportion of photogenerated carriers releasing photons through radiative recombination increases, while the loss through non-radiative recombination of defect states decreases. The improvement in PLQY directly reflects the reduction in the density of defect states inside and on the surface of the film, especially the effective suppression of deep-level recombination centers. Simultaneously, the QFLS of the treated film also increases, indicating a higher degree of separation between electron and hole quasi-Fermi levels under illumination, allowing carriers to maintain a higher effective chemical potential difference, thus reducing non-radiative voltage loss. Therefore, these results not only demonstrate that NH₄Cl vapor phase treatment improves the luminescence efficiency and carrier recombination behavior of the CsPbI₂Br film, but also show that it is beneficial for increasing the open-circuit voltage and upper limit of photoelectric conversion efficiency of the device.
[0082] 4. XRD analysis was used to analyze the crystal structure and crystallinity of CsPbI2Br perovskite in the untreated and NH4Cl gas-phase treated states, such as... Figure 4 As shown.
[0083] from Figure 4 It can be seen that both the untreated and NH4Cl vapor-phase treated CsPbI2Br films exhibited characteristic diffraction peaks of CsPbI2Br, mainly corresponding to the (100), (110), and (200) crystal planes, and no obvious new impurity phase peaks were observed, indicating that the NH4Cl vapor-phase treatment did not destroy the main crystal phase of CsPbI2Br. Compared with the untreated sample, the characteristic peak intensities of the NH4Cl-treated sample were significantly enhanced, especially the peak intensities of the (100) and (200) crystal planes. This result indicates that the crystallinity of the CsPbI2Br film is improved after NH4Cl vapor-phase treatment, the crystal orientation is more obvious, and the disordered crystallization and defect-related structures in the film are reduced. Combined with the aforementioned in-situ UV-vis and in-situ PL results, it can be seen that the NH3 released by NH4Cl can delay the rapid nucleation and phase transformation process, allowing the lattice more time to arrange itself in an orderly manner, thereby obtaining a CsPbI2Br film with higher crystal quality.
[0084] 5. SEM images of untreated and NH4Cl vapor-phase treated CsPbI2Br films were tested separately.
[0085] The results are as follows Figure 5 As shown, from Figure 5 It can be seen that the surface of the untreated sample consists of a large number of small grains with dense grain boundaries; while the grains of the sample treated with NH4Cl gas phase are significantly larger, with larger grain size and fewer grain boundaries. Figure 5The particle size statistics for c and d further indicate that the perovskite particle size distribution shifts towards a larger size range after NH4Cl vapor phase treatment, with a decrease in the proportion of small grains and an increase in the proportion of large grains. As the grains grow, the number of grain boundaries in the film decreases accordingly, which helps reduce defect accumulation and carrier recombination losses at grain boundaries and suppresses ion migration along grain boundaries, thus positively impacting film quality, carrier transport, and device stability.
[0086] 6. Cross-sectional SEM images of CsPbI2Br perovskite solar cell devices after untreated and NH4Cl gas phase treatment were performed respectively.
[0087] The results are as follows Figure 6 As shown, some grain boundary penetrations and local discontinuities can be observed in the cross-section of the untreated CsPbI₂Br film, indicating that the crystal growth was insufficient during rapid crystallization, and there is still room for improvement in the longitudinal compactness and interfacial contact of the film. In contrast, the perovskite film treated with NH₄Cl has a more continuous and dense cross-section, better uniformity in perovskite layer thickness, more complete longitudinal grain growth, and reduced internal porosity and obvious fracture defects, indicating that vapor phase treatment is beneficial to improving the bulk crystallization quality of the CsPbI₂Br film.
[0088] 7. The surface roughness of CsPbI2Br perovskite films after untreated and NH4Cl vapor phase treatment was analyzed using AFM testing.
[0089] from Figure 7 As can be seen, the untreated CsPbI₂Br film has a large surface undulation with significant height differences between grains, and an RMS roughness of 28.8 nm, indicating that the film surface uniformity and density are still insufficient. In contrast, the perovskite film treated with NH₄Cl has a smoother surface, reduced local height undulations, and an RMS roughness reduced to 23.2 nm. The corresponding height profile also shows that the surface fluctuation of the perovskite film treated with NH₄Cl is smaller, indicating that the film surface is smoother and the grain connection is more continuous.
[0090] from Figure 8 As can be seen, the untreated CsPbI₂Br film exhibits significant surface undulations, with noticeable peaks and depressions, indicating uneven crystal growth and poor surface smoothness during rapid crystallization. In contrast, the perovskite film treated with NH₄Cl shows a marked reduction in surface undulations and a more concentrated surface height distribution, indicating a smoother and more uniform surface. Lower surface roughness facilitates uniform contact of subsequent carbon electrodes or interface layers, reduces local interface defects and leakage channels, thereby improving carrier transport, reducing recombination losses, and enhancing device stability.
[0091] Example 3: Passivation of CsPbI2Br perovskite defects with NH4Cl and surface chlorination characterization
[0092] This embodiment mainly explores the effects of NH4Cl treatment on the distribution of halide-related ions and changes in the chemical state of perovskite surfaces. The specific content is as follows:
[0093] 1. The distribution of halide-related ions in CsPbI2Br films under different NH4Cl treatments was characterized using TOF-SIMS. Among them, PbI3... - and PbBr3 - It mainly reflects the distribution of the main components of CsPbI2Br perovskite, PbCl3 - It can be used to characterize the distribution of Cl-related passivation components in thin films, F - The signal mainly originates from the FTO substrate, such as Figure 9 As shown.
[0094] from Figure 9 a and Figure 9 As can be seen from c, after liquid phase treatment with NH4Cl, PbCl3 - The overall signal is weak and unevenly distributed, indicating that Cl passivation is mainly concentrated on the film surface. However, some solution penetrates downwards along grain boundaries, pores, or defect channels, even reaching the lower interface. This demonstrates a problem of shallow treatment depth but significant local penetration, and may cause secondary dissolution or interface disturbance on the perovskite surface. In contrast, Figure 9 b and Figure 9 PbCl3 after gas phase treatment - The stronger and more continuous signal distribution indicates that the HCl / Cl active components generated by the NH4Cl gas phase can act more uniformly on the surface, grain boundaries, and bulk region of the CsPbI2Br film, thereby achieving more complete passivation of Cl-related defects and helping to suppress halide ion migration and improve the stability of the film and device. Compared with solution treatment, gas phase treatment can avoid solvent-induced surface damage and passivating agent distribution fluctuations, and achieve a more uniform passivation effect.
[0095] 2. The chemical states of the CsPbI2Br perovskite surface after untreated and NH4Cl gas phase treatment were analyzed using XPS. The results are as follows: Figure 10 As shown.
[0096] from Figure 10 It can be seen that after NH4Cl gas-phase treatment, the characteristic peaks of Cs 3d, Pb 4f, I 3d, and Br 3d in the CsPbI2Br film all showed slight shifts, indicating that gas-phase treatment altered the local chemical environment of the perovskite surface and grain boundaries. This change mainly originates from the interaction between Cl-related components and perovskite defect sites. Because Cl... - Radius less than I- and Br - It is easier for Cl to enter halogen vacancies at the surface and grain boundaries; at the same time, Cl has a higher electronegativity than Br and I, and can bind with uncoordinated Pb. 2+ This leads to stronger Pb-Cl interactions. The formation of Pb-Cl bonds alters the electron cloud distribution around Pb, reducing the electron cloud density at the Pb site and causing a shift in the Pb 4f binding energy towards higher binding energies, indicating that uncoordinated Pb... 2+ Effective passivation was achieved. Simultaneously, the changes in the peak positions of I 3d and Br 3d indicate that the halogen coordination environment was readjusted, and halogen vacancy defects were compensated. These results demonstrate that NH4Cl gas-phase treatment can stabilize the surface and grain boundaries through Cl-related passivation structures, reduce Pb-related defects and halogen vacancy defects, thereby reducing nonradiative recombination and suppressing ion migration.
[0097] 3. Raman spectroscopy was used to analyze the chemical bonds of CsPbI₂Br perovskites in both untreated and NH₄Cl gas-phase treated samples, such as... Figure 11 As shown.
[0098] from Figure 11 It can be seen that the Raman peak in the low wavenumber region mainly originates from the lattice vibrations of the CsPbI2Br inorganic lead halide framework, with the 57 cm⁻¹ peak being the most prominent. -1 The appearance of the peak indicates that [PbI6] was treated with the gas phase. 4- The (X=I / Br / Cl) octahedral network is more pronounced, indicating that the inorganic framework structure of the thin film has been optimized. 279 cm -1 The peak at [location] shifted, which can be attributed to the Pb-Cl related vibration. In CsPbI₂Br perovskite treated with NH₄Cl, this peak redshifted to 269 cm⁻¹. -1 This indicates that Cl-related components have participated in the local coordination environment at the surface or grain boundaries of CsPbI₂Br, forming Pb-Cl interactions. The shift of the peak position to lower wavenumbers usually signifies that the Pb-Cl vibration is in a locally distorted environment different from the ideal Pb-Cl bond, possibly related to mixed I / Br coordination, changes in halogen ratios, and passivation of defects at grain boundaries. In other words, Cl is not simply adsorbed on the surface, but rather interacts with uncoordinated Pb. 2+ Interactions may occur at Pb sites near halogen vacancies, thereby altering the local vibrational modes of the Pb-X octahedron. Therefore, Raman's results indicate that NH4Cl vapor-phase treatment has two positive effects on CsPbI2Br films: firstly, it optimizes [PbI6]... 4- The octahedral inorganic framework structure enhances lattice order; secondly, the introduction of a Pb-Cl-related passivation structure modulates the Pb-X coordination environment at the surface and grain boundaries, thereby helping to reduce halogen vacancies and uncoordinated Pb. 2+Defects, reduce nonradiative recombination and suppress ion migration.
[0099] 4. The activation energies of CsPbI2Br perovskite ions after untreated and NH4Cl gas-phase treatment were analyzed using conductivity measurements, such as... Figure 12 As shown.
[0100] Both untreated and NH4Cl-treated CsPbI2Br perovskites exhibited approximately linear IV relationships at different temperatures, with the current increasing with temperature, indicating thermally activated ion / carrier transport in the film. Compared to the untreated sample, the NH4Cl-treated CsPbI2Br perovskite showed a larger current response and a higher IV curve slope at the same voltage and temperature, indicating higher overall conductivity and lower transport resistance. Further calculations of the ion migration activation energy based on the Arrhenius relation were performed, such as... Figure 12 As shown in Figure c, the activation energy for ion migration in the untreated sample is 0.25 eV, while that of the CsPbI₂Br perovskite treated with NH₄Cl gas phase increases to 0.36 eV. A higher activation energy indicates that I₂PbI₂Br perovskite exhibits higher ion migration activity. - / Br - The greater the energy barrier that halide ions need to overcome for migration, the less likely they are to migrate under the influence of heat, light, and built-in electric fields. Therefore, this result shows that NH4Cl vapor phase treatment not only improves the effective charge transport capability of the thin film, but also suppresses unfavorable halide ion migration. This is beneficial for reducing hysteresis, phase separation, and interface degradation, thereby enhancing the operational stability of the device.
[0101] 5. UV-vis testing was used to analyze the separation of the CsPbI2Br perovskite phases after untreated and NH4Cl gas phase treatment, such as... Figure 13 As shown.
[0102] from Figure 13The results show that the untreated sample exhibits more significant absorption changes in the 600-640 nm region during continuous illumination, indicating that the untreated CsPbI₂Br film is more prone to halogen ion migration and component redistribution under illumination, thereby inducing local phase separation or structural degradation. In contrast, the CsPbI₂Br film treated with NH₄Cl shows weaker absorption changes in the same wavelength range, indicating that its light-induced halogen migration and phase separation are suppressed, and the film has better phase stability. After illumination, the film is immersed in toluene. The solution of the untreated sample is darker in color and shows a more obvious absorption signal in the UV-vis spectrum, indicating that more halogen-related degradation products or migrating components are extracted by toluene after illumination. The solution of the CsPbI₂Br sample treated with NH₄Cl is very light in color, with almost no significant reduction in absorption signal, indicating that the film treated with NH₄Cl is less prone to halogen migration, phase separation, and structural decomposition under illumination. Based on the aforementioned characterization results, it can be seen that the Cl-related passivation structure can compensate for halogen vacancies, enhance Pb-Cl interactions, and increase the ion migration barrier, thereby effectively improving the photo-stability of CsPbI2Br films.
[0103] 6. Photoluminescence mapping (PL) was performed on CsPbI2Br films after untreated and NH4Cl vapor phase treatment, respectively. The results are as follows: Figure 14 As shown.
[0104] from Figure 14 As can be seen, the PL mapping of the untreated CsPbI₂Br film exhibits significant unevenness in brightness and darkness, with numerous localized low-intensity regions, indicating uneven distribution of crystallization and defects, and strong localized nonradiative recombination. In contrast, the PL signal distribution of the CsPbI₂Br film treated with NH₄Cl is more continuous and uniform, with a significant reduction in low-intensity regions and more stable overall luminescence intensity. This result demonstrates that NH₄Cl gas-phase treatment can delay rapid crystallization and promote ordered crystal rearrangement by NH₃, while passivating surface and grain boundary defects through HCl / Cl-related components, thereby obtaining a more uniform CsPbI₂Br film with fewer defects. Gas-phase treatment is more conducive to achieving uniform passivation, improving PL intensity, and reducing nonradiative recombination.
[0105] 7. The carrier recombination behavior of untreated and NH4Cl gas-phase treated CsPbI2Br thin films was analyzed using TRPL testing. The results are as follows: Figure 15 As shown.
[0106] from Figure 15The results show that the photogenerated carrier (PL) decays rapidly in the untreated sample, with an average lifetime of 11.93 ns, indicating the presence of numerous defect states in the film, leading to rapid loss of photogenerated carriers via nonradiative recombination. In contrast, the PL decay of the sample treated with NH4Cl significantly slows down, with an average lifetime increasing to 19.26 ns. These results demonstrate that NH4Cl gas-phase treatment can effectively passivate defects, suppress nonradiative recombination, facilitate the transport and collection of photogenerated carriers, and prolong carrier lifetime, thereby improving the quality of CsPbI2Br films.
[0107] 8. The local current distribution and conductivity uniformity of the CsPbI2Br film surface after untreated and NH4Cl vapor phase treatment were analyzed using c-AFM testing. The results are as follows: Figure 16 , 17 As shown.
[0108] from Figure 16 The results show that the average current of the untreated sample is 66.44 pA, with relatively low local current distribution and greater fluctuations in the current response along the scan line. This indicates that certain grain boundary defects, trapped states, or local transport obstacles still exist in the film, resulting in insufficient carrier transport at the film surface / grain boundaries. In contrast, the average current of the CsPbI2Br film treated with NH4Cl increased to 77.34 pA, and the overall current response along the scan line was higher and less volatile, indicating that the local conductivity of the film was enhanced and carrier transport was smoother after vapor phase treatment.
[0109] from Figure 17 As can be seen, the three-dimensional current map of the untreated sample shows a generally low current level, while the CsPbI2Br film treated with NH4Cl exhibits a more continuous high current plateau, with the current distribution shifting towards higher values. This is not simply due to a few high current points, but rather an overall increase in current over a larger scanning area. This indicates that NH4Cl treatment improves the overall conductivity uniformity of the film, rather than a localized, accidental enhancement. Therefore, the treated film forms a more uniform and continuous current transport network, which is beneficial for improving carrier extraction efficiency, reducing the risk of interfacial recombination and localized leakage, and ultimately promoting improved device efficiency and stability.
[0110] 9. The local potential distribution and uniformity of the CsPbI2Br film surface after untreated and NH4Cl vapor phase treatment were analyzed using KPFM testing. The results are as follows: Figure 18 , 19 As shown.
[0111] from Figure 18It can be seen that the average surface potential of the untreated CsPbI₂Br film is 0.36 V, while that of the CsPbI₂Br film treated with NH₄Cl in the gas phase increases to 0.50 V. This indicates that the gas phase treatment alters the electronic structure and local potential distribution of the perovskite film surface. An increase in surface potential typically indicates a reduction in trapped states on the film surface, a modulation of the Fermi level position, and a decrease in recombination losses of photogenerated carriers in the surface region.
[0112] from Figure 19 It can be seen from the 3D KPFM image that the surface potential of the CsPbI2Br film after NH4Cl vapor phase treatment shifts to a higher potential region overall, indicating that this potential increase is not a localized, accidental phenomenon, but rather occurs generally within a large scanning area. This result shows that NH4Cl vapor phase treatment can improve the electronic uniformity of the film surface, reduce potential fluctuations caused by local defects and grain boundaries, and facilitate the formation of more continuous charge transport and extraction channels. The Cl-related passivation structure formed after NH4Cl vapor phase treatment can interact with uncoordinated Pb... 2+ Interactions occur, compensating for halogen vacancies and thus reducing charge trapping induced by surface defects. Ultimately, this increase and homogenization of the surface potential helps enhance the built-in electric field, promote carrier separation, and reduce interfacial recombination losses, thereby supporting improvements in open-circuit voltage and device stability.
[0113] 10. Electron-only SCLC analysis was used to analyze the electron transport capability, trap filling confinement voltage, and defect state density of untreated and NH4Cl vapor-phase treated CsPbI2Br films. The results are as follows: Figure 20 As shown.
[0114] from Figure 20 It can be seen that both the untreated and NH4Cl-treated CsPbI2Br electronic devices exhibit typical SCLC characteristics. The low-voltage region is mainly the ohmic transport region; as the voltage increases, the current increases rapidly and enters the trap-fill confinement region. Compared to the untreated sample, the trap-fill confinement voltage V of the NH4Cl-treated CsPbI2Br is significantly higher. TFL The decrease from 1.55 V to 1.47 V indicates that the number of defect states that need to be filled in the thin film has decreased, and the trapping effect on electrons during transport has weakened. Figure 20 b's J 1 / 2 The -V fitting results show that the slope of CsPbI2Br after NH4Cl gas phase treatment is slightly higher, corresponding to an increase in electron mobility from 4.43 × 10⁻⁶. -2 cm 2 V -1 s -1 Increased to 4.68×10 -2 cm 2 V -1s -1 This indicates that the electron transport capability of the thin film was improved after NH4Cl gas-phase treatment. Consequently, its trapped state density increased from 5.71 × 10⁻⁶. 15 cm -3 Reduced to 3.68×10 15 cm -3 This indicates that vapor phase treatment effectively reduced the electron trap density inside the thin film and at the grain boundaries.
[0115] 11. The Urbach energy of untreated and NH4Cl vapor-phase treated CsPbI2Br films was analyzed using UV-vis testing, such as... Figure 21 As shown.
[0116] from Figure 21 As can be seen, both the untreated and NH4Cl-treated CsPbI2Br films exhibit the typical absorption characteristics of CsPbI2Br perovskite, with the absorption edge positions being basically consistent, indicating that NH4Cl treatment did not significantly alter the bulk band gap and crystal structure of CsPbI2Br. Compared to the untreated film, the absorption intensity of the NH4Cl-treated CsPbI2Br film in the visible light region is slightly improved, indicating that the crystallinity and light absorption capacity of the film are improved after vapor phase treatment. Figure 21 b. Further calculation of the Urbach energy based on the exponential tail states near the absorption edge. The Urbach energy E0 of the untreated CsPbI2Br thin film. u The Urbach energy was 54.84 meV, while it decreased to 48.15 meV after NH4Cl vapor phase treatment of the CsPbI2Br film. A smaller Urbach energy indicates a steeper absorption edge, fewer band tail states, and a lower degree of energy disorder in the film. This result demonstrates that NH4Cl vapor phase treatment can reduce structural disorder, lattice distortion, and defect-induced band tail states in CsPbI2Br films, thereby reducing defect-assisted nonradiative recombination and voltage drop.
[0117] Example 4: Performance Testing of All-Inorganic CsPbI2Br Perovskite Solar Cells Passivated by NH4Cl Vapor-Phase Assisted Crystallization
[0118] 1. The all-inorganic CsPbI2Br perovskite solar cell device with NH4Cl vapor-phase assisted crystallization passivation prepared in Example 1 has an FTO / SnO2-TiO structure. x Cl 4-2x The / CsPbI2Br / carbon electrode is used for electrochemical characterization, as shown in the following example. Figure 22 As shown.
[0119] from Figure 22As can be seen from Figure a, compared with the untreated CsPbI2Br device, the JV curve of the device after NH4Cl gas-phase treatment is improved overall, indicating that gas-phase treatment can effectively improve the photovoltaic output performance of the device, with a maximum photoelectric conversion efficiency of 15.53%. This improvement mainly comes from the aforementioned improvements in thin film quality, reduction in defect density, and enhancement in carrier transport. Figure 22 Figures b and c show the forward and reverse scan JV curves. It can be seen that the overlap between the forward and reverse scan curves of the device is higher after NH4Cl gas phase treatment, and the hysteresis index is reduced from 29.80% to 21.57%. This indicates that NH4Cl gas phase treatment can suppress ion migration and interface charge accumulation, thereby reducing the device hysteresis phenomenon.
[0120] Figure 22 In the test results, the EQE response and integral current of the device after NH4Cl gas phase treatment matched the JV test results. The error between the integral current and the short-circuit current was controlled within 5%, indicating that the device current output is reliable. Figure 22 The steady-state output results of the device show that after NH4Cl gas phase treatment, the device can maintain a more stable current density and efficiency output near the maximum power point, indicating that the device's operating stability is improved after gas phase treatment. Figure 22 The Mott-Schottky results for f show that the built-in potential of the device is increased after NH4Cl gas phase treatment, indicating that gas phase treatment helps to enhance the built-in electric field and promote the separation and transport of photogenerated carriers. Figure 22 The Nyquist plots of g and h further show that the device has a larger recombination resistance under both light and dark conditions after NH4Cl gas phase treatment, indicating that interfacial recombination and bulk defect recombination are suppressed. Figure 22 As shown in Figure i, the dark current of the device decreases after NH4Cl vapor phase treatment, which also indicates that the leakage channels are reduced and defect-assisted recombination is weakened.
[0121] In summary, NH4Cl gas-phase treatment delays the rapid crystallization of CsPbI2Br, promotes grain growth, and passivates halogen vacancies and uncoordinated Pb. 2+ Ultimately, this improved the thin film crystal quality and interfacial electrical properties. Its positive impacts at the device level manifest as higher photoelectric conversion efficiency, lower hysteresis, stronger carrier separation capability, greater recombination resistance, and lower dark current, thus contributing to improved efficiency and long-term stability of CsPbI2Br perovskite solar cells.
[0122] 2. The stability of CsPbI2Br films after untreated and NH4Cl vapor phase treatment was analyzed by aging tests under environmental conditions, such as... Figure 23 As shown.
[0123] from Figure 23The results show that, under conditions of 25 °C and 50-60% RH, the untreated CsPbI₂Br film exhibited significant color changes and surface degradation with prolonged exposure. Localized lightening and spotting were observed after 4 hours, and the degraded areas gradually expanded. After 24 hours, large-scale fading and decomposition marks appeared, indicating poor stability under humid conditions. In contrast, the film treated with NH₄Cl maintained better overall color and surface integrity within 0-15 hours. Although some degradation occurred after 24 hours, the degree was significantly lower than that of the untreated sample. These results demonstrate that NH₄Cl gas-phase treatment can significantly delay the degradation process of CsPbI₂Br films in humid air.
[0124] 3. Under continuous illumination ISOS-L-1 test conditions, the stability of untreated and NH4Cl gas-phase treated CsPbI2Br perovskite solar cell devices was analyzed, such as... Figure 24 As shown.
[0125] from Figure 24 The results show that the normalized PCE of the untreated device decays rapidly with operating time, maintaining only 71.49% of the initial efficiency after 347 h; while the device treated with NH4Cl gas phase decays significantly slower, maintaining 75.50% of the initial efficiency after 670 h of continuous illumination. This indicates that NH4Cl gas phase assisted treatment can significantly improve the illumination-assisted operation stability of CsPbI2Br perovskite solar cells.
[0126] 4. Under test conditions of 25 ℃, humidity below 5% RH, and protection from light, the storage stability of untreated and NH4Cl gas-phase treated CsPbI2Br perovskite solar cell devices was analyzed. Figure 25 As shown.
[0127] from Figure 25 The results show that after 172 days of storage, all photovoltaic parameters of the untreated device degraded to varying degrees over time, with PCE and FF showing the most significant degradation, ultimately remaining at 51.60% and 72.08% of their initial values, respectively. This indicates that the device experienced significant interface degradation, increased defects, or impaired charge transport during storage. In contrast, the device treated with NH4Cl gas phase exhibited better storage stability, with V... oc PCE, J sc The initial values of FF and NH4Cl were maintained at 93.92%, 87.30%, 93.63%, and 99.28%, respectively, with a significant slowdown in the degradation of each parameter. These results indicate that NH4Cl vapor phase treatment not only improves the initial device performance but also effectively suppresses performance degradation during storage.
[0128] 5. Under ISOS-D-2 test conditions of 85 ℃, the dark storage stability of CsPbI2Br perovskite solar cell devices after untreated and NH4Cl gas phase treatment was analyzed, and the results are as follows: Figure 26 As shown.
[0129] from Figure 26 As can be seen, after 48 days of storage, all photovoltaic parameters of the untreated device showed significant degradation, with PCE and FF showing the most significant decline, ultimately remaining at 55.41% and 75.27% of their initial values, respectively. This indicates that under high-temperature conditions, halide ion migration, defect increase, and interface degradation occurred within the device, leading to enhanced carrier recombination and hindered charge transport. In contrast, the device treated with the NH4Cl phase exhibited better thermal stability, V oc PCE, J sc The FF values of the CsPbI2Br perovskite solar cells remained at 91.80%, 80.58%, 92.60%, and 94.81% of their initial values, respectively, with significantly smaller degradation rates than the control device. This result demonstrates that NH4Cl vapor-phase treatment can effectively improve the stability of CsPbI2Br perovskite solar cells under high-temperature conditions.
[0130] In summary, this invention proposes a method for fabricating high-efficiency CsPbI₂Br perovskite solar cells based on inorganic ammonium salt vapor-phase assisted crystallization passivation. Its innovation lies in introducing solid NH₄Cl as a vapor-phase control source into the CsPbI₂Br annealing and crystallization process, allowing it to release NH₃ and HCl active atmospheres in situ under heating conditions, thus constructing a non-contact treatment system of "solid ammonium salt - vapor-phase active component - perovskite thin film". This method differs from traditional solution additives or post-solution treatments, as it does not damage the already formed perovskite surface and avoids problems such as solvent residue, localized over-passivation, and uneven distribution of passivating agents. It has the advantages of simple process, uniform effect, and easy scale-up fabrication.
[0131] This invention utilizes NH4Cl gas-phase assisted treatment to obtain high-efficiency CsPbI2Br perovskite solar cells. The NH3 molecules released during the treatment process possess lone pairs of electrons and can act as Lewis bases to react with uncoordinated or poorly coordinated Pb in CsPbI2Br. 2+ Reversible coordination occurs, forming a Pb-NH3 interaction or transient coordination intermediate. This reversible coordination can reduce Pb levels. 2+ The rapid reaction rate with halogen components slows down the rapid nucleation and crystallization process of perovskites, increases the migration time of precursor ions and crystal rearrangement time, thereby promoting grain growth and improving the crystallization quality of thin films; on the other hand, NH3 promotes the growth of uncoordinated Pb at the surface and grain boundaries. 2+It has a passivating effect, which can reduce Pb-related deep-level defects and decrease nonradiative recombination of charge carriers. As subsequent high-temperature annealing proceeds, the weakly coordinated NH3 gradually desorbs or volatilizes from the film, preventing the formation of a large amount of insulating residue in the perovskite lattice, which is beneficial to maintaining the intrinsic charge transport characteristics of CsPbI2Br.
[0132] Meanwhile, the HCl gaseous component released by NH4Cl can introduce Cl-related passivation structures on the perovskite surface and at grain boundaries. Cl- can preferentially act on halogen vacancies and Pb-enriched defect sites, filling or compensating for halogen vacancies and interacting with uncoordinated Pb. 2+ Strong Pb-Cl interactions are formed, constructing Cl-enriched passivation layers or chloride passivation structures on the perovskite surface and grain boundaries. Due to the relatively strong Pb-Cl bond energy, this chloride passivation layer can increase the formation energy of halogen defects at the surface and grain boundaries, hinder the migration channels of halide ions such as I- / Br-, and suppress ion migration, phase segregation, and interface degradation under light and thermal stress.
[0133] This invention uses FTO conductive glass as a substrate and sequentially prepares a SnO2 electron transport layer, a TiCl4 post-treatment layer, a CsPbI2Br perovskite light-absorbing layer, and a carbon electrode. After spin-coating a CsPbI2Br precursor to form a mesophase film, an inorganic ammonium salt is placed in a closed chamber and preheated to generate a gaseous environment containing ammonia and hydrogen halides. This allows the perovskite mesophase film to undergo short-term assisted crystallization and surface / grain boundary passivation in the gaseous environment. Subsequently, high-temperature annealing yields a high-quality CsPbI2Br film. Further fabrication yields a high-efficiency CsPbI2Br perovskite solar cell with an open-circuit voltage of 1.15~1.33V and a short-circuit current of 12mA·cm⁻¹. -2 ~14.8 mA·cm -2 The fill factor is 0.70~0.82, and the photoelectric conversion efficiency is 13%~15.5%. This invention employs gas-phase assisted processing to synergistically regulate the crystallization kinetics of CsPbI₂Br, reducing defect density, minimizing non-radiative recombination, and improving device stability. This invention features a simple and low-cost process, is compatible with the fabrication process of carbon electrode all-inorganic perovskite solar cells, and has excellent potential for device performance improvement and large-scale application.
[0134] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions claimed by the present invention.
Claims
1. A method for fabricating an all-inorganic CsPbI2Br perovskite solar cell based on inorganic ammonium salt vapor-phase assisted crystallization passivation, characterized in that, The preparation method specifically includes the following steps: (1) Preparation of SnO2 quantum dot solution: SnCl2 and thiourea were dissolved in deionized water and stirred, centrifuged, precipitate removed, and filtered to obtain SnO2 quantum dot solution; (2) Preparation of SnO2 electron transport layer: The SnO2 quantum dot solution and FTO conductive glass are preheated respectively. After preheating, the SnO2 quantum dot solution is spin-coated onto the FTO conductive glass to obtain FTO / SnO2 substrate; (3) TiCl4 modification treatment: The FTO / SnO2 substrate was placed in a TiCl4 aqueous solution for water bath treatment, followed by rinsing and annealing to obtain FTO / SnO2-TiO2. x Cl 4-2x A basis, where x ≤ 2; (4) Preparation of CsPbI2Br precursor solution: CsI, PbI2 and PbBr2 are dissolved in a polar organic solvent to obtain CsPbI2Br precursor solution; (5) Preparation of CsPbI2Br mesophase thin film: The CsPbI2Br precursor solution was spin-coated onto the FTO / SnO2-TiO2 film. x Cl 4-2x On the substrate, hot air assisted film formation was performed during spin coating to obtain a CsPbI2Br mesophase film; (6) Preparation of CsPbI2Br perovskite film: Inorganic ammonium salt is placed in a closed chamber for preheating treatment to release gas and form a gas phase treatment environment; the CsPbI2Br mesophase film is placed in the gas phase treatment environment for gas phase assisted crystallization passivation treatment, and after the passivation treatment is completed, it is heated and annealed to obtain CsPbI2Br perovskite film. (7) Carbon electrode preparation: Carbon paste is coated on the CsPbI2Br perovskite film and heated for annealing to obtain an all-inorganic CsPbI2Br perovskite solar cell.
2. The preparation method according to claim 1, characterized in that, In step (1), the molar ratio of SnCl2 to thiourea is 0.8~1.2:1, and the molar concentration of SnCl2 is 0.1 mol / L~0.5 mol / L.
3. The preparation method according to claim 1, characterized in that, The preheating temperature of the SnO2 quantum dot solution in step (2) is 70°C. o C~90 o C, the preheating time is 3 min to 9 min; the preheating time of the FTO conductive glass is 1 min to 5 min; the spin coating speed is 1000 to 2000 rpm, and the spin coating acceleration is 500 to 1200 rpm / s.
4. The preparation method according to claim 1, characterized in that, In step (3), the volume concentration of the TiCl4 aqueous solution is 400 μL / mL to 600 μL / mL, and the temperature of the water bath treatment is 60°C. o C~100 o C. The water bath treatment time is 20 min to 50 min.
5. The preparation method according to claim 1, characterized in that, In step (4), the molar ratio of CsI, PbI2 and PbBr2 is 1.8~2.2:0.8~1.2:0.8~1.
2.
6. The preparation method according to claim 1, characterized in that, In step (5), the spin coating adopts a two-step spin coating process, specifically including: the first step spin coating: the rotation speed is 500 rpm to 2000 rpm, and the time is 5 s to 20 s; the second step spin coating: the rotation speed is 2500 rpm to 5000 rpm, and the time is 20 s to 60 s.
7. The preparation method according to claim 1, characterized in that, In step (6), the inorganic ammonium salt includes NH4Cl. The temperature of the preheating treatment is 150 ℃~170 ℃ and the time of the preheating treatment is 3 min~8 min. The time of the gas phase assisted crystallization passivation treatment is 40 s~100 s.
8. The all-inorganic CsPbI2Br perovskite solar cell prepared by any of the preparation methods described in claims 1 to 7.
9. The application of the all-inorganic CsPbI2Br perovskite solar cell according to claim 8 in the preparation of solar cell modules, photovoltaic power generation devices, portable power supply devices or power stations.
10. The application according to claim 9, characterized in that, The open-circuit voltage of the all-inorganic CsPbI2Br perovskite solar cell is 1.15~1.33V, and the short-circuit current is 12 mA·cm⁻¹. -2 ~14.8 mA·cm -2 The fill factor is 0.70~0.82, and the photoelectric conversion efficiency is 13%~15.5%.